Oxygen reduction reaction catalyzed by carbon composites with ruthenium-doped iron oxide nanoparticles. Issue 11 (19th April 2022) - Liu, Qiming; Zhou, Hong Bo; Nichols, Forrest; Kuo, Han-Lin; Mercado, Rene; Lu, Bingzhang; Zhu, Weiya; Liu, Yashu; Lu, Jennifer Q.; Bridges, Frank; Chen, Shaowei
Abstract : Carbon nanocomposites with Ru-doped Fe2 O3  nanoparticles are derived from a Fe–Ru–Fe trinuclear complex and zeolitic imidazolate framework 8 and exhibit excellent electrocatalytic activity towards oxygen reduction reaction, comparable to that of Pt/C. Abstract : Carbon nanocomposites based on transition-metal oxides have been attracting extensive attention as cost-effective catalysts towards the oxygen reduction reaction (ORR). However, the activity remains subpar as compared to state-of-the-art platinum catalysts. One way to enhance the ORR performance is to dope a second metal into the nanocomposite to manipulate the electronic structure and hence the interactions with key reaction intermediates. Herein, dual metal (Ru and Fe) and nitrogen codoped carbon (RuFe-NC) nanocomposites were synthesized by controlled pyrolysis of a Fe–Ru–Fe trinuclear complex along with zeolitic imidazolate framework-8. The obtained porous nanocomposites consisted of Ru-doped Fe2 O3 nanoparticles embedded within a carbon scaffold, and exhibited an ORR activity in alkaline media rivaling that of commercial Pt/C, which was also markedly better than those of the monometallic counterparts and nanocomposites prepared with a simple mixture of the individual monometallic compound precursors. Structural characterization suggests that the use of the trinuclear complex facilitated the atomic dispersion of ruthenium within the iron oxide nanoparticles and charge transfer between the metal centers led to a high ORR activity. Results from this study suggest that rational design of heteronuclear complexes may be a unique strategy in the structural engineering of carbon-metal nanocomposites for high-performance electrocatalysis.